The Influence of Corporate Culture on Job Engagement of Employees in Travel Companies in Hanoi - Duc, Bui Huu; Anh, Le Thi Tu (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
: To quickly recover from the Covid-19 pandemic, travel companies are trying to find effective ways to improve employee engagement and stabilize human resources in the long term. This paper examines the influence of corporate culture on the job engagement of employees based on the survey results of 193 employees in travel companies in Hanoi. The analysis results show that the five aspects of corporate culture mentioned have a positive influence on job engagement. The paper discusses the results and provides implications for managers in developing corporate culture for employee engagement improvement.